Peningkatan Kecerdasaan Logika Matematika Anak melalui Bermain Kartu Angka Kelompok B di TK Pembina Bangkinang Kota - Mufarizuddin Mufarizuddin (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
This research is in background not yet developed ability of logic mathematics intelligence of child of group B TK Pembina Bangkinang Kota. Based on the background of the problems that have been exposed, it can be formulated problem of this research, How to improve the ability of logic mathematics intelligence of group B through the game of card number in TK Pembina Bangkinang Kota? The purpose of this study is to determine the enhancement of the ability of logic mathematical intelligence through the game of number cards in group B in TK Pembina Bangkinang Kota. As the subjects in this study are the children of group B and teachers kindergarten coach 2015/2016 school year with the number of children as many as 20 people. While the object is the ability of logic mathematical intelligence of group B through the game of a number card. The steps taken in classroom action research are: 1) Planning / Preparing for action, 2) Implementation of Action, 3) Observation, and 4) Reflection. The data sources of this research are children of group B TK Pembina Bangkinang Kota, teachers and documents. Data collection uses observation, tests and documentation. Data analysis using descriptive technique percentage. The results showed that through the card number can improve the ability of logic mathematical intelligence in group B TK Pembina Bangkinang Kota.